The Impacts of Depression Treatment on Health-Related Quality of Life in Cancer Patients: A Systematic Review - Andrik Hermanto; Gabriel Wanda Sinawang; Mohamad Roni Alfaqih; Rohmatul Faizah (Universitas Airlangga, 2019)
Introduction: Cancer diagnosis can have a profound negative impact on the health-related quality of life (HRQoL) of cancer patients. Cancer patients also suffer from psychological pressures including sadness, depression, hopelessness, anxiety and worry. The literature review was employed to determine the effects of depression on health-related quality of life (HRQoL) in cancer patients.Methods: A systematic review was conducted by searching the Science Direct, Scopus and Google Scholar databases. The integrative review of the 10 articles was focused on the 10 years period from 2008 to 2018. The language used was English and the search was conducted using predefined keywords.Results: All of the journals discussed the impact of depression treatment on health-related quality of life in cancer patients. Based on all of the journals, depression can be reduced by health education, physical activity and medicine therapyConclusion: Despite the treatment for depression, the patient’s HRQoL did not improve during the measurement timeframe. Quality of life is a priority health outcome in cancer treatment but the clinical approaches to ameliorate depression in cancer patients appear to be suboptimal.